Effects of Norway Spruce (Picea abies) Stump Debarking on Insect Colonization in the Polish Sudety Mountains - Iwona Skrzecz; Joanna Ukalska; Dorota Tumialis (Mountain Research and Development, 2016)
This study aimed to determine whether debarking of Norway spruce stumps influences the intensity of their colonization by insects. The observed stumps of Picea abies (L.) H Karst were located in the eastern Sudety Mountains at elevations between 600 and 1000 meters above sea level (masl) on clear-cut areas where large-diameter timber and small logging slash had been harvested. In total, 720 fresh (up to 12 months old) P. abies stumps were investigated, of which half were debarked immediately after tree felling. Insects were collected from 0.5 m2 bark samples taken from coarse roots around the stump base and then identified with regard to family, genus, and species. P. abies stumps were colonized by insects from 18 families from 2 orders: Coleoptera and Diptera. Coleopterans were most frequently represented by the families Cerambycidae (52% of all collected insects) and Curculionidae (41%), including the subfamily Scolytinae (15%). Approximately 1.5% of all insects collected were classified as Diptera. Overall, approximately 40% greater insect colonization was observed in the bark samples collected from debarked P. abies stumps. The debarking treatment increased the intensity of stump colonization by both Cerambycidae and Scolytinae but had no effect on colonization by Curculionidae (excluding Scolytinae). These results suggest that debarking Norway spruce stumps does not reduce insect colonization and could be avoided in forest management.